HIPERPORNOGRAFI PEREMPUAN DALAM IKLAN - Ervan Ismail (Jurnal Visi Komunikasi, 2015)
Research by the author is using the critical paradigm is based on the notion that a variety of issues related to the hyper-pornography emerged from the audience understandings of social reality constructed by advertising. Type of research is a descriptive study using semiotic analysis. Data was collected to make a second record Geliga Muscle Cream ads and Malkis Abon as primary data. Secondary data obtained through the study of literature in the form of books, journals and internet sites.In the second survey results revealed the ad has a depth of meaning that leads to hyper-pornography completely after carefully using the theory of Jean Baudrillard was found that the two ads is the result of the simulation and produce effects that lead women toward kekecenderungan hiperpornografi, based on the results of the study, the second theme ad lifting sensation will be a sign that women's sexuality is the most dominant in the second ad. This advertising system refers to Hollywood movies, one movie Devil Wear Prada and also a novel by Tami Hoag "Luck's Lady". Genre film and the novel is fiction fantasy and romantic drama-crafted by a writer or a director and writer.Penelitian yang dilakukan penulis adalah menggunakan paradigma kritis didasarkan pada pemikiran bahwa berbagai hal yang berkaitan dengan hiper-pornografi muncul dari pemahaman-pemahan sosial khalayak yang terkonstruksi oleh realitas iklan. Jenis penelitian yang dilakukan adalah penelitian deskriptif dengan menggunakan analisis semiotika. Teknik pengumpulan data dilakukan dengan membuat rekaman kedua iklan Krim Otot Geliga dan Malkis Abon sebagai data primer. Data sekunder didapat melalui studi literatur berupa buku, jurnal dan situs internet.Pada hasil penelitian diketahui pada kedua iklan memiliki kedalaman makna yang mengarah kepada hiper-pornografi seutuhnya setelah di teliti menggunakan teori Jean Baudrillard didapati bahwa kedua iklan adalah hasil dari simulasi dan menghasilkan efek yang mengarahkan perempuan menuju kekecenderungan hiperpornografi, berdasarkan hasil penelitian, Tema kedua iklan yang mengangkat sensasi akan seksualitas perempuan adalah tanda yang paling dominan di kedua iklan. Sistem iklan ini merujuk kepada film-film Hollywood, salah satunya film Devil Wear Prada dan juga sebuah novel karangan Tami Hoag “Luck’s Lady”. Genrenya film dan novel tersebut adalah fiksi fantasi dan romantis drama yang dikarangoleh seorang pengarang ataupun seorang sutradara dan penulis